PKM-PENGEMBANGAN WILAYAH BAGI POKDARWIS KAMPUNG INGGRIS JOGJA SEBAGAI KAMPUNG WISATA EDUKASI DI SAPEN, GONDOKUSUMAN, KOTA YOGYAKARTA - Maria Lies Endarwati; Anita Mustikasari; Donald Jupply Nababan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract Sapen Village as an educational tourism destination was initiated in 2019 by the community leaders of Sapen Village adopting the patterns and systems of the English Village of Pare, Kediri, East Java. However, current conditions and developments are still far from being expected to boost the local economy. From the results of interviews with the initiators and movers, as well as observations in the community, it was found that there were obstacles, one of which was that the management of Pokdarwis was still conventional; For this reason, it is necessary to provide knowledge about business management. In the Independent Learning Program for the Independent Campus and the Main Performance Indicators of Higher Education, students and lecturers are required to think more critically, analytically, and creatively. So that the empowerment of Pokdarwis Kampung English Jogja as an Educational Tour can become a chamber of commerce, a Youth Center which will further benefit the development of MSME actors in Yogyakarta in supporting the movement of the economy, especially in Sapen Village, Kemantren Gondokusuman, Yogyakarta City. Therefore, this activity provides direction to partners on the importance of tourism business management for Pokdarwis in supporting the success of educational tourism in Sapen, Kemantren Gondokusuman and also facilitates tourism management assistance for Pokdarwis FGDs or facilitates partners related to English learning programs and modules Abstrak Kampung Sapen sebagai tujuan wisata edukasi dirintis sejak tahun 2019 oleh tokoh masyarakat Kampung Sapen mengadopsi pola dan sistem dari Kampung Inggris Pare, Kediri, Jawa Timur. Namun saat ini kondisi dan perkembangannya masih terbilang sangat jauh dari harapan untuk mendongkrak perekonomian warga. Dari hasil wawancara dengan penggagas dan penggerak, serta observasi di masyarakat, ditemukan hambatan, yaitu salah satunya adalah manajemen pengelolaan Pokdarwis masih konvensional; untuk itu perlu diberikan pengetahuan mengenai manajemen pengelolaan usaha. Pada Program Merdeka Belajar Kampus Merdeka dan Indikator Kinerja Utama Perguruan Tinggi, mahasiswa dan dosen dituntut untuk lebih berpikir kritis, analitis, dan kreatif. Sehingga pemberdayaan Pokdarwis Kampung Inggris Jogja sebagai Wisata Edukasi ini dapat menjadi kamar dagang, Youth Centre yang selanjutnya akan bermanfaat bagi pengembangan pelaku UMKM di Yogyakarta dalam menopang gerak laju perekonomian terutama di Kampung Sapen, Kemantren Gondokusuman, Kota Yogyakarta. Oleh karena itu kegiatan ini memberikan pengarahan kepada mitra akan pentingnya manajemen usaha wisata bagi Pokdarwis dalam menunjang kesuksesan wisata edukasi di Sapen, Kemantren Gondokusuman dan juga menfasilitasi pendampingan pengelolaan wisata bagi Pokdarwis FGD atau menfasilitasi mitra terkait program dan modul pembelajaran Bahasa Inggris